Long-Term Anamnesis of Chronic Thromboembolic Pulmonary Disease. Does it Predict the Results of Pulmonary Thromboendarterectomy? (London Journal of Medical and Health Research, 2025)
Introduction: Pulmonary thromboendarterectomy (PEA) is the main method of treatment for patients with chronic thromboembolic pulmonary hypertension (CTEPH). The residual pulmonary hypertension (PH) after CTEPH surgical treatment is a risk factor with increasing of hospital mortality.Objective: To analyze and evaluate the results of PEA in patients with different persistent time of medical history as a possible prognostic factor of residual PH and outcome.Methods: Retrospective and prospective analysis of the PEA results in 87 patients operated on from April 2012 to February 2022 was conducted. The patients were divided into 3 groups. The 1st group - 45 patients with a medical history from 3 months to 1 year, the 2nd - 20 patients from 1 year to 3 years and the 3rd - 22 patients with long-term history more than 3 years.Results: The average age of the patients was 48.7 13.5 years, including 56.7 % males and 43.3 % females. Due to New York Heart Association (NYHA), 7 (8.0%) patients preoperatively belonged to class II, 60 (69.0%) to class III and 20 (23.0%) to class IV. Postoperatively the mean pulmonary artery pressure (mPAP mmHg) and pulmonary vascular resistance (PVR dynscm??) significantly decreased in all groups (mPAP :1st group from 4513 to 236, 2 nd from 4914 to 256 and 3 rd from 5812 to 317; PVR: 1st group from 797262 to 290135, 2 nd from 925383 to 376159 and 3 rd from 1248332 to 505189). Hospital mortality after PEA was 0 in patients with medical history less than 1 year, 5% from 1 to 3 years and 31% in patients with long- term anamnesis.Conclusions: PEA is an effective surgery with mPAP and PVR decreasing in the early postoperative period. However, long-term medical history and PVR >1000 dynscm?? are very important risk factors with increasing of hospital mortality.
Keywords: Quality improvement; brazil; organ transplantation; management program; PAT-MA; health systems; Maranh; pulmonary hypertension.; Chronic thromboembolic pulmonary hypertension; Thrombendarterectomy; Pulmonary vascular resistance; Long-term medical history.